2010
DOI: 10.1111/j.1365-2672.2009.04464.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of bacterial lipopolysaccharide (LPS) as an immunostimulant for the control ofAeromonas hydrophilainfections in rainbow troutOncorhynchus mykiss(Walbaum)

Abstract: Aims:  To determine the effect of lipopolysaccharide (LPS) for the prevention of infection by Aeromonas hydrophila in rainbow trout (Oncorhynchus mykiss Walbaum) fingerlings. Methods and Results:  Rainbow trout fingerlings were fed with 0 mg (= controls), 1·875 mg, 3·75 mg, 7·5 mg and 15 mg of LPS per 100 g of commercial feed for 14 days before experimental challenge with A. hydrophila. The results revealed a reduction in mortalities to 5% in the two lowest doses and 15% in the group, which received 15 mg LPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 51 publications
9
46
0
Order By: Relevance
“…For example, LPS, which is a component of the outer cell wall membrane of Gram-negative bacteria, possesses immunogenic properties, and a small dose (i.e., mg ml À1 ; Iliev et al [34]) can induce the production/activation of antibody, lysozyme, alternative complement pathway, B and T lymphocytes, cytokines like interleukin (IL)-2 and -6, pro-inflammatory cytokines like IL-1b, tumour necrosis factor (TNF)-a and several other factors from macrophages, including phagocytic activity in fish [35,36]. OMPs of Gram-negative bacteria are also known to be immunodominant antigens, and may provoke strong humoral and cellular immune responses in fish [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…For example, LPS, which is a component of the outer cell wall membrane of Gram-negative bacteria, possesses immunogenic properties, and a small dose (i.e., mg ml À1 ; Iliev et al [34]) can induce the production/activation of antibody, lysozyme, alternative complement pathway, B and T lymphocytes, cytokines like interleukin (IL)-2 and -6, pro-inflammatory cytokines like IL-1b, tumour necrosis factor (TNF)-a and several other factors from macrophages, including phagocytic activity in fish [35,36]. OMPs of Gram-negative bacteria are also known to be immunodominant antigens, and may provoke strong humoral and cellular immune responses in fish [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that low concentration of LPS could be beneficial to fish for enhancing non-specific immune responses such as phagocytic activity and proliferation of B and T lymphocytes [14]. Rock bream is a commercially important fish in marine aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial, lysozyme and phenoloxidase activities were significantly increased when crab Scylla paramamosain was challenged with bacterial LPS (Nya andAustin 2010, Gopalakrishnan et al 2011). The results of this study showed that LPS had a similar effect on Malabar grouper and could be a potential effective immunostimulant for it.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), an essential component of the cell wall of Gram-negative bacteria, can effectively improve the non-specific immunity of aquatic and terrestrial animals and is widely used as an immunostimulant to control their infectious diseases (Nya and Austin 2010). Jian et al (2004) reported that, after injection of LPS for 28 days, the immunity of many aquatic animals was significantly improved.…”
Section: Introductionmentioning
confidence: 99%